1996
DOI: 10.1111/j.1600-051x.1996.tb00580.x
|View full text |Cite
|
Sign up to set email alerts
|

Biostimulation of wound healing by low‐energy laser irradiation A review

Abstract: This paper reviews studies on the basic principles of biostimulation of wound healing by various low-energy lasers. It looks at the mechanism of action of biostimulation as well as the laser's effect on cell proliferation, collagen synthesis, and would healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
287
2
20

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 428 publications
(318 citation statements)
references
References 22 publications
9
287
2
20
Order By: Relevance
“…These findings suggest that this protocol of light Laser irradiation is able to downregulate the inflammatory response and favor the acceleration of biological events responsible for the healing process. Similar findings attesting a remarkable anti-inflammatory activity of LLLT in other different protocols have been previously reported 14,15 . Additionally, LLLT apparently influenced the dynamic of the immunoinflammatory response at early stages of wound healing process, once it clearly induced switching of the leukocyte infiltration pattern (neutrophilic to lymphoplasmacytic infiltration) into the damaged tissue of irradiated wounds.…”
Section: Discussionsupporting
confidence: 91%
“…These findings suggest that this protocol of light Laser irradiation is able to downregulate the inflammatory response and favor the acceleration of biological events responsible for the healing process. Similar findings attesting a remarkable anti-inflammatory activity of LLLT in other different protocols have been previously reported 14,15 . Additionally, LLLT apparently influenced the dynamic of the immunoinflammatory response at early stages of wound healing process, once it clearly induced switching of the leukocyte infiltration pattern (neutrophilic to lymphoplasmacytic infiltration) into the damaged tissue of irradiated wounds.…”
Section: Discussionsupporting
confidence: 91%
“…Increased amount of collagen fibers was reported previously following several laser therapy protocols. 30,38,39 Similarly, studies carried out using polarized light sources also reported positive biomodulatory effects on wound healing. 22,40,41 Polarized light may reproduce nearly 80% of the effects of the laser, but nonpolarized light may not.42 Polarization has also been suggested as an important factor on tissue responses.26,43 Despite earlier reports suggesting that laser light may inhibit or have no effect on wound healing, meticulous analysis of evidence and problems on the parameters used30,44-48 or consequence of the systemic effect of the laser therapy remain.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported-beneficial effects of LLLT on chronic wound healing, in healthy and nonhealthy rats, as well as in some other small animals. 7,10,[19][20][21][22] Since blood flow is increased in the microcirculation during laser therapy, this could explain the enhancement of wound healing and reduced pain. 6,7 Others have suggested that LLLT is beneficial for wound healing in diabetics.…”
Section: Discussionmentioning
confidence: 99%
“…14 Laser parameters (such as wavelength, time of exposure, and dosage) used for in vivo studies of the effect of LLLT on wound healing have not been standardized yet. 11,20 It is difficult to compare results from different experiments when laser parameters are variable.…”
Section: Introduction Dmentioning
confidence: 99%